Brand promotion through digital marketing: how digital marketing enhance consumer engagement & develop relationship with clients and consumer. - Khondokar, Golam Ishtiaq (BRAC University, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.